Nano-pulling stimulates axon regeneration in dorsal root ganglia by inducing stabilization of axonal microtubules and activation of local translation - Falconieri, Alessandro; Folino, Pietro; Da Palmata, Lorenzo; Raffa, Vittoria (Frontiers in Molecular Neuroscience, 2024)
Introduction Axonal plasticity is strongly related to neuronal development as well as regeneration. It was recently demonstrated that active mechanical tension, intended as an extrinsic factor, is a valid contribution to the modulation of axonal plasticity. Methods In previous publications, our team validated a the “nano-pulling” method used to apply mechanical forces to developing axons of isolated primary neurons using magnetic nanoparticles (MNP) actuated by static magnetic fields. This method was found to promote axon growth and synaptic maturation. Here, we explore the use of nano-pulling as an extrinsic factor to promote axon regeneration in a neuronal tissue explant. Results Whole dorsal root ganglia (DRG) were thus dissected from a mouse spinal cord, incubated with MNPs, and then stretched. We found that particles were able to penetrate the ganglion and thus become localised both in the somas and in sprouting axons. Our results highlight that nano-pulling doubles the regeneration rate, and this is accompanied by an increase in the arborizing capacity of axons, an accumulation of cellular organelles related to mass addition (endoplasmic reticulum and mitochondria) and pre-synaptic proteins with respect to spontaneous regeneration. In line with the previous results on isolated hippocampal neurons, we observed that this process is coupled to an increase in the density of stable microtubules and activation of local translation. Discussion Our data demonstrate that nano-pulling enhances axon regeneration in whole spinal ganglia exposed to MNPs and external magnetic fields. These preliminary data represent an encouraging starting point for proposing nano-pulling as a biophysical tool for the design of novel therapies based on the use of force as an extrinsic factor for promoting nerve regeneration.